93.7k views
4 votes
Multiply: (4x – 7)(2x – 9)

User Rites
by
5.6k points

2 Answers

2 votes
(4x−7)(2x−9)
=(4x+−7)(2x+−9)
=(4x)(2x)+(4x)(−9)+(−7)(2x)+(−7)(−9)
=8x236x14x+63
=8x250x+63
User Crandel
by
5.9k points
7 votes
Hello there!


Let's use foil.

First: 4x * 2x = 8x^2

Outside: 4x * -9 = -36x

Inside: -7 * 2x = -14x

Last: -7 * -9 = 63

Now, let's combine these.

8x^2 - 36x - 14x + 63

Finally, we can simplify this

8x - 50x + 63



I hope I helped!

Let me know if you need anything else!

~ Zoe
User Riley Bracken
by
6.9k points